The use of medical health applications by primary care physicians in Israel: a cross-sectional study - Menashe Meni Amran; Avital Bilitzky; Mattan Bar-Yishay; Limor Adler (BMC, 2024)
Abstract Background The use of medical health applications (mHealth apps) by patients, caregivers, and physicians is widespread. mHealth apps are often employed by physicians to quickly access professional knowledge, guide treatment, easily retrieve medical records, and monitor and manage patients. This study sought to characterize the use of mHealth apps among primary care physicians (PCPs) in Israel. The reasons for using apps and barriers to their use were also investigated. Methods From all MHS' PCPs, we randomly selected 700 PCPs and invited them to complete a questionnaire regarding the use of mHealth apps and attitudes toward them. Results From August 2020 to December 2020, 191 physicians completed the questionnaire (response rate 27.3%). 68.0% of PCPs reported using mHealth apps. Telemedicine service apps were the most frequently used. Medical calculators (used for clinical scoring) and differential diagnosis apps were the least frequently used. The most common reason for mHealth app use was accessibility, followed by time saved and a sense of information reliability. Among infrequent users of apps, the most common barriers reported were unfamiliarity with relevant apps and preference for using a computer. Concerns regarding information reliability were rarely reported by PCPs. Physician gender and seniority were not related to mHealth app use. Physician age was related to the use of mHealth apps. Conclusions mHealth apps are widely used by PCPs in this study, regardless of physician gender or seniority. Information from mHealth apps is considered reliable by PCPs. The main barrier to app use is unfamiliarity with relevant apps and preference for computer use.